2007
DOI: 10.1074/jbc.m701100200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Activating Receptor LMIR4 as a Counterpart of Inhibitory Receptor LMIR3

Abstract: The leukocyte mono-Ig-like receptor (LMIR) belongs to a new family of paired immunoreceptors. In this study, we analyzed activating receptor LMIR4/CLM-5 as a counterpart of inhibitory receptor LMIR3/CLM-1. LMIR4 is expressed in myeloid cells, including granulocytes, macrophages, and mast cells, whereas LMIR3 is more broadly expressed. The association of LMIR4 with Fc receptor-␥ among immunoreceptor tyrosinebased activation motif-bearing molecules was indispensable for LMIR4-mediated functions of bone marrow-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
115
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(118 citation statements)
references
References 56 publications
3
115
0
Order By: Relevance
“…The 3 0 UTR was cloned to downstream of the Renilla luciferase stop codon in pGL4.74 vector (Promega, Madison, WI, USA). To generate the mutant 3 0 UTR of the mouse Trp53inp1, two-step PCR mutagenesis was performed [24][25][26] using the WT-3 0 UTR as a template. The Rluc-2 Â 125b site vector contained two copies of a sequence designed to be perfectly complementary to the miR125b downstream of the Renilla luciferase stop codon.…”
Section: Luciferase Assaymentioning
confidence: 99%
“…The 3 0 UTR was cloned to downstream of the Renilla luciferase stop codon in pGL4.74 vector (Promega, Madison, WI, USA). To generate the mutant 3 0 UTR of the mouse Trp53inp1, two-step PCR mutagenesis was performed [24][25][26] using the WT-3 0 UTR as a template. The Rluc-2 Â 125b site vector contained two copies of a sequence designed to be perfectly complementary to the miR125b downstream of the Renilla luciferase stop codon.…”
Section: Luciferase Assaymentioning
confidence: 99%
“…Paired immune receptors are generally composed of several activating and inhibitory receptors with high homology in the extracellular domains (1,2). We have previously characterized leukocyte mono-Ig-like receptors 1-5 (LMIR1-5) 3 among a novel paired receptor family called LMIR/CMRF-35-like molecules (CLMs)/myeloid-associated Ig-like receptor (MAIR)/ dendritic cell-derived Ig-like receptor (DIgR)/CD300 (3)(4)(5)(6)(7)(8)(9). LMIR3/CLM-1/MAIR-V/DIgR2/CD300LF is an inhibitory receptor that possesses an ITIM in the cytoplasmic region (4,6,7,10,11).…”
mentioning
confidence: 99%
“…We have previously characterized leukocyte mono-Ig-like receptors 1-5 (LMIR1-5) 3 among a novel paired receptor family called LMIR/CMRF-35-like molecules (CLMs)/myeloid-associated Ig-like receptor (MAIR)/ dendritic cell-derived Ig-like receptor (DIgR)/CD300 (3)(4)(5)(6)(7)(8)(9). LMIR3/CLM-1/MAIR-V/DIgR2/CD300LF is an inhibitory receptor that possesses an ITIM in the cytoplasmic region (4,6,7,10,11). On the other hand, LMIR4/CLM-5 or LMIR5/CLM-7, which is an activating receptor paired with LMIR3, associates with an ITAM-containing adaptor protein, FcR␥ or DNAX activating protein of 12 kDa (DAP12), respectively (4,11,12).…”
mentioning
confidence: 99%
“…To date, various important molecules have been detected including SDF-1, a member of the tumor necrosis factor receptor superfamily TROY, Xenopus-Tsukushi, Vasorin and leukocyte mono-Ig-like receptor (LMIR) by the SST method (18)(19)(20)(21)(22)(23). In this study, we identified a secreted molecule ADAMTS4 (a disintegrin and metalloproteinase with thrombospondin motifs) from EWS cell lines by using the SST system based on retrovirus-mediated expression screening (SST-REX) (24,25).…”
Section: Introductionmentioning
confidence: 99%